The impact of Middle East on the German literature - Dhahir, Thamer Abdulkareem (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to show how the oriental nation affected the GERMAN literature as it affected other nation's culture and literature. In these pages we can see how the conflict was and what the current position is the opinion of European most great German authors such as Harder and Goethe, which distinguish Arabic oriental literary life from the west part of the glop where armies vividly occupied eastern Arabic lands through their power the Arabs got rid of the Superficiality and looked deeper into their own identification. German writers tried to reach the essence of Islamic civilization as well as the essence of Arabic poetry and the religious spirit in the East literature on the contrary of the German literature also religious translations that attracted the attention of writers in Germany. Eastern equestrian spirit which influencing Arab poetry, the poetry in Europe became an essential part of chivalrous life. Fairy tales like One Thousand and One Nights, Tragedy of AL Mansour also and mix of the two techniques, the oriental traditional East and the nontraditional European, Goethe believes that Arab literature reached a peak in the Middle Ages that only Greek and Roman literature reached before them, our research contains The opinion of a German translator Stefan Weidner who said that since the 1970s, we can note that Germany has become an increasingly attractive target for Arab immigrants so we see our honorable great writers whom affected the German literary life from Egypt, Iraq, Lebanon, Syria and Palestine. Many of them preferred permanent residency in Germany, chose to contribute to German and Arab cultural life, and in many cases, played the role of mediator between the two cultures.